PERTANIAN MENGHADAPI PEREKONOMIAN GLOBAL - Sutawi, Sutawi (Jurnal Bestari, 2002)
Global economic, trade, investment and financial sector have opened the market worldwide. Global business rule are being harmonized in some international forums. As result of globalization, there are two important thing i.e. the wider market and the more player  in the global business. This will bring a consequence  that a nation, a company, and a business sector will face a tight competition. To make a higher  competitiveness, there is no other way but making products, including agriculture products, more efficient. There are serious problem faced by Indonesian  agriculture. The problem are that opening up agriculture markets may hurt developing  country-agriculture, and also vulnerable groups within them. Higher and more volatile food prices hurt consumers, while poor farmer may be displayed by imports of cheap food. Indonesian agriculture will stand to lose from economic globalization. Critics of globalization suggest that developing countries  will become less sufficient and more dependent on other countries and that trade will be concentrated in the hand of developed countries.